Assessment of maternal risk factors associated with low birth weight neonates at a tertiary hospital, Nalgonda - Reddy, V. Mounika; Tanneru, Shreya; Thomas, Suresh R. J. (International Journal of Contemporary Pediatrics, 2021)
Background: Low birth weight continues to be the major cause of neonatal morbidity and mortality in developing countries. Birthweight and gestational age are important factors for survival, growth, and overall development of the child. In India, the prevalence of low birthweight has decreased from 20.4% to 16.5% in last decade.1 Although the prevalence of LBW neonates in India has declined over past decade, the extent of decline is only modest. Therefore, there is still need for the study of modifiable risk factors associated with low birth weight. The objective of the study was to identify the maternal risk factors associated with low birth weight in the babies admitted to Kamineni Institute of Medical Sciences, Narketpally. Methods: A hospital based observational study was carried out in Kamineni Institute of Medical Sciences among 91 mother/newborn pairs using interviewer administered questionnaire. Results: This study revealed that 29.67% infants were born low birth weight. The risk of LBW was higher among mothers of age<20 years (16.48%) and BMI<18.5 kg/m2 (17.58%). Mothers who are anemic (21.98%) and suffering from chronic maternal illness (15.38%) were at high risk of giving birth to low birth weight baby. The likelihood of giving LBW baby was higher among multiparous (18.68%) than primiparous women. Conclusions: The prevalence of low birth weight was found to be very high and it was associated with many risk factors related to maternal health. Hence it is recommended to improve maternal health through strengthening the existing maternal services at the basic level of community.